Estimation of evaluation some spirometric's parameters of football players during preparation period - Fortuna, Małgorzata; Szczurowski, Jacek; Zabłocki, Tomasz; Pałasz, Dagmara; Demczyszak, Iwona (Journal of Education, Health and Sport, 2018)
IntroductionSpirometric parameters are influenced by, among other things level of fitness. Aim:The aim of the study was to evaluate the formation of selected spirometric parameters of the football players in the preparatory period.Material and methods:The selected spirometry parameters FVC, FVC%, FEV1, FEV1%, FEV1 / VC were evaluated in 20 players 17-18 years old. The results were related to the value of the reference population studies. The evaluation was performed at the beginning and at the end of preparatory period. Results and Conclusions: Preparation players in the preparatory period does not increase significantly the level of respondents respiratory parameters FVC, FVC%, FEV1, FEV1%. The three-month training of football players during the preparation period does not significantly increase the level of respiratory parameters tested.